The Influence of Teachers’ Metacognitive Skills and Classroom Management On Students’ Learning Motivation at SMA Negeri 2 Beo, Talaud Islands Regency - Jurni Pande; Jefry Sony Junus Lengkong; Mozes M. Wullur; Romi J. Mongdong (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of teachers’ metacognitive skills and classroom management on students’ learning motivation at SMA Negeri 2 Beo. The main issues underlying this research are low student participation, lack of concentration during learning activities, and minimal initiative in completing academic tasks. The study employed a quantitative method with a survey approach involving 30 respondents selected through Proportional Random Sampling from a total population of 88 students. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The partial test results (t-test) indicate that teachers’ metacognitive skills have a significant effect on learning motivation, with a t-value of 3.653 > t-table of 2.052 (sig. 0.001). Similarly, classroom management shows a significant effect, with a t-value of 4.876 > t-table of 2.052 (sig. 0.019). Simultaneously (F-test), both variables significantly influence learning motivation, with an F-value of 8.252 > F-table of 3.35 (sig. 0.002). The coefficient of determination (R Square) of 0.679 indicates that these two variables contribute 67.9% to the variance in students’ learning motivation. In conclusion, teachers’ ability to plan and evaluate their own thinking processes (metacognition), combined with effective classroom management strategies, is a crucial factor in enhancing students’ learning motivation. Schools are recommended to provide continuous training for teachers to optimize these competencies.